Alliance activity as a dynamic capability in the face of a discontinuous technological change - Anand, Jaideep (2010)
Using a dynamic capabilities lens, this study examines how technological and complementary capabilities affect firms’ abilities to enter emerging technologies. The empirical evidence from a sample of pharmaceutical firms entering the new biotech fields indicates that both technological and complementary capabilities potentially affect firms’ entry into emerging technologies and entry mode. However, the results also show that capabilities in the traditional technology and the emerging technology have different effects. Firms with capabilities in the emerging technology are more likely to enter new technological fields and more likely to use internal development in doing so. Complementary capabilities also increase the rate of entry into emerging technological fields. However, capabilities in traditional technology are found to be unrelated to the propensity to enter new fields, and to the choice of entry mode. These results are consistent with insights from the literature on dynamic capabilities and evolutionary theory. We examine the implications of these results for literatures on strategic alliances and technological competition.